Contributions of Ibn-Sina in pharmaceutical sciences - Jusoh @ Abd Rashid , Rusila Zamani; Shafie, Amir Akramin (IIUM Press, 2011)
This chapter investigates about the contribution ofIbn-Sina in pharmaceutical sciences. Ibn-Sina was the most famous physician, philosopher, encyclopaedist, mathematician and astronomer at his time. The objective of this chapter is to investigate the contribution of Ibn-Sina in pharmaceutical sciences through his book; The Canon of Medicine. Ibn-Sina is chosen among Muslims Scientists because of these reasons: Ibn-Sina is a simply best represents the Iranian-Islamic scientific culture and medicine in history and he is a well recognized and respected in science and medicine throughout the world. The methodology adopted in this chapter is library based research and data is collected from reliable sources such as articles, journals and books. This chapter explores the findings of Ibn-Sina that using different methods of medications and treatment in pharmaceutical sciences